2008
DOI: 10.1590/s0034-76122008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Administração pública e gestão social: a produção científica brasileira entre 2000 e 2005

Abstract: Sumário: 1. Introdução; 2. Produção científica em administração; 3. Procedimentos metodológicos; 4. Descrição e análise de dados; 5. Considerações finais.Su m m a ry : 1. Introduction; 2. Scientific production in administration; 3. Methodological procedures; 4. Data description and analysis; 5. Final remarks.Pa l av r a S -c h av e : administração pública; gestão social; metodologia de pesquisa; pesquisa acadêmica; produção científica. Key w o r d S :public sector management; social management; research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
2
6
0
2
Order By: Relevance
“…In addition to the aforementioned works, when Fleury, Bloch, Bravo, and Bicudo (2003) analyzed articles published in the Public Administration Magazine (Revista de Administração Pública [RAP]), between 1992 and 2002, he observed that case study was a research strategy used in 32% of the articles reviewed. Findings discovered by Hocayenda-Silva, Rossoni and Ferreira (2008) confirm this observation. Gondim et al (2005) …”
Section: Academic Production In Public Administrationsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition to the aforementioned works, when Fleury, Bloch, Bravo, and Bicudo (2003) analyzed articles published in the Public Administration Magazine (Revista de Administração Pública [RAP]), between 1992 and 2002, he observed that case study was a research strategy used in 32% of the articles reviewed. Findings discovered by Hocayenda-Silva, Rossoni and Ferreira (2008) confirm this observation. Gondim et al (2005) …”
Section: Academic Production In Public Administrationsupporting
confidence: 63%
“…Among the articles first selected, only those that had predominantly qualitative empirical research as their objective were All the articles selected were initially analyzed according to their contexts, making it possible to identify the period of publication, the journals that published the greater part of the material, as well as the institutions that had the highest output on the subject. Then, based on the outline of previous research on administration published in Brazil (Bertero, Caldas, & Wood, 1999;Bertero, Vasconcelos, & Binder, 2003;Calixto, 2009;Gondim et al, 2005;Hocayen-da-Silva, Rossoni, & Ferreira, 2008;Pacheco, 2003;Tonelli, Caldas, Lacombe, & Tinoco, 2003;Vergara & Peci, 2003), the following general analysis criteria were used: (a) number of case studies investigated; (b) selection strategy used in each case; (c) temporal cut-off; (d) level of governmental research on the subject; (e) data gathering technique; (f) data analysis technique; and (g) theoretical basis.…”
Section: Methodsmentioning
confidence: 99%
“…Since the late 1980s, Brazilian PA research shares with its American counterpart the systematic attempt at self-evaluation. However, this self-evaluation process began later in the Brazilian context, with a paper by Machado-Da-Silva, Amboni, and Cunha in 1989 (Machado-Da-Silva et al., 1989), followed by other evaluations that mainly demonstrate that the academic field of PA in Brazil lacks institutional quality and maturity, even though it is growing exponentially (Hocayen-da-Silva et al., 2008; Machado-da-Silva et al., 2008; Pacheco, 2003).…”
Section: Pa Research In the North American And Brazilian Contextsmentioning
confidence: 99%
“…To examine the state of PA research, we analyze, through a content analysis of a sample of highly ranked Brazilian journal publications, the subjects that PA researchers regularly study, the paradigmatic cognitive orientations of the publications, their methodological refinement, and their institutional characteristics, and compare these dimensions to previous North American evaluations. Our focus on Brazilian PA research is justified not only by the exponential growth of the field of PA in terms of the numbers of graduate-school programs, academic meetings, researchers, academic journals, and publications (Hocayen-da-Silva et al., 2008; Machado-Da-Silva et al., 1989; Pacheco, 2003; Souza, 1998), but also by the relevance of Brazil and its public sector in terms of the global economy.…”
Section: Introductionmentioning
confidence: 99%
“…Estas análises apontam problemas reincidentes relacionadas, principalmente, com a: (a) falta de rigor metodológico; (b) concentração excessiva da produção em poucas instituições e número relativamente reduzido de redes de pesquisa; além da (c) importação de matriz teórica, refletida na baixa diversidade de origem de autoria e alta citação de autores norte-americanos; e, (d) falta de relevância das pesquisas realizadas (Bertero & Keinert, 1994;Caldas & Tinoco, 2004;Hocayen-da-Silva, Rossoni, & Ferreira, 2008a, 2008bMachado-da-Silva, Cunha, & Amoboni, 1990;Rodrigues & Carrieri, 2001;Quintella, 2003;Vergara & Pinto 2001) (3) .…”
Section: Sobre O Vácuo Epistemológico Do Campo De Administraçãounclassified